Cadmium Phytoremediation by Arundo donax L. from Contaminated Soil and Water. (28th December 2013) - Sabeen, Maria; Mahmood, Qaisar; Irshad, Muhammad; Fareed, Iftikhar; Khan, Afsar; Ullah, Farid; Hussain, Jamshaid; Hayat, Yousaf; Tabassum, Sobia
Abstract : The potential of Arundo donax L. for phytoextraction of cadmium (Cd) from contaminated soil and water was probed. The plants were grown under greenhouse conditions in pots containing a nutrient solution or soil with increasing doses of Cd (0, 50, 100, 250, 500, 750, and 1000  μ g L −1 ) for 21 days. The growth and physiology of plants were evaluated at the end of the experiment. The maximum Cd content in root was 300  μ g g −1 during hydroponics experiments over 230  μ g g −1 in soil experiment. Cd concentration in stem was 262  μ g g −1 at 750  μ g L −1 supplied Cd in hydroponics over 191.2  μ g g −1 at 1000 in soil experiment. The maximum Cd concentration in leaves from hydroponics was 187  μ g g −1 . Relatively low Cd uptake occurred during soil experiment with low translocation factor (TF) values. Both Bioaccumulation Factor (BF) and TF values for hydroponics were greater than 1. The IC50 values of ABTS and DPPH showed that both time and increasing Cd concentrations affected the production of antioxidants with lower half maximal inhibitory concentration (IC50 ) value on the 21st days. A. donax showed better potential for Cd remediation of aquatic environments.